Public debt - Economic growth nexus in the WAMZ: Are there different components threshold effects? - Olorunsola E. Olowofeso; Ebrima N. Wadda; Adegoke I. Adeleke; Joseph R. Yengbe; Yaya Cham; Tapia M. Kanu (West African Monetary Institute (WAMI), 2023)
This study presents novel empirical evidence on the optimal disaggregated public debt-growth threshold in the WAMZ over the period 1996-2022. Determining the public debt-growth threshold in a disaggregated form is crucial for macroeconomic policy measures in the region to curb high public debt levels that can diminish the ability of governments to cushion adverse shocks. Although there is considerable empirical literature on this subject, previous studies generally focused only on total public debt or external debt components, while ignoring the impacts of domestic debt and debt service on the economies of the region. The estimated results clearly indicate that most components of public debt have inherent negative effects on per capita income. Furthermore, they show that domestic debt appears to have less negative dampening effects on economic growth than external debt. This outcome supports the recent shift by WAMZ countries from foreign debt to more domestic debt due to the relative ease of debt mobilization. Similarly, the results from panel threshold models indicate a threshold value of 87.45 percent of GDP for total public debt, 12.71 percent for external public debt, 46.94 percent for domestic public debt, and 17.80 percent for total debt service, all of which are statistically significant at different levels. These findings suggest that implementing a mix of fiscal and monetary policy measures to ensure that all components of the public debt-to-GDP ratio remain below their threshold levels would support economic growth. Above these thresholds, all components of the public debt-to-GDP ratio would be harmful to growth. The findings provide strong empirical support for the policy stance of the WAMZ convergence criterion to contain public debt at less than or equal to 70 percent, which is also reflected in the debt-growth nonlinear relationship.
Keywords: E62; O47; C23; 330; Public Debt; Growth; Panel Data Models; Threshold Effects; West Africa